Highly conductive carbon-coated aluminum foil and process for producing the same
Patent Information
- Application Number
- CN202611166273.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]为解决现有技术中存在的界面电阻高、碳材料易团聚、导电聚合物稳定性差、工艺不环保等问题,本发明提供了一种高导电性涂碳铝箔及其制备工艺
(1)本发明通过对铝箔表面进行脉冲电化学刻蚀,形成孔径250-400nm、深度0.3-0.8μm的微坑形貌,涂覆碳涂层后,碳涂层表面复制了该微坑形貌,从而在碳涂层表面形成微坑结构,同时在碳涂层浆料中添加柠檬酸。由此,微坑结构增加了碳涂层与铝箔的接触面积,形成物理嵌合;柠檬酸分子中的羧基与铝箔表面的氧化铝层形成化学配位。物理嵌合与化学配位协同提高界面结合强度,降低了电子在碳涂层与铝箔之间界面处的传输阻力,从而使界面接触电阻得以显著下降,为1.5-1.9mΩ·cm2。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and more particularly to a highly conductive carbon-coated aluminum foil and its preparation process. Background Technology
[0002] Carbon-coated aluminum foil refers to a composite material formed by coating an aluminum foil surface with a carbon-containing conductive coating. It is widely used in electrochemical energy storage devices such as lithium-ion batteries and supercapacitors, and is commonly used as a positive electrode current collector. In lithium-ion batteries, the positive electrode active materials (such as lithium iron phosphate and ternary materials) have poor conductivity. Directly coating them onto the aluminum foil surface results in a large interfacial contact resistance, leading to increased internal resistance, intensified polarization, and decreased rate performance. Carbon-coated aluminum foil, by introducing a conductive carbon coating between the aluminum foil and the positive electrode active material, can reduce interfacial contact resistance and improve electron collection efficiency, thereby improving the battery's charge-discharge performance and cycle life. Therefore, how to further improve the conductivity of carbon-coated aluminum foil is a continuously attracting technical focus in this field.
[0003] Currently, the main technical approaches to improving the conductivity of carbon-coated aluminum foil include carbon material compounding, binder modification, functional additives, aluminum foil surface treatment, and conductive polymer composites. Specifically, carbon material compounding involves combining carbon materials of different dimensions, such as conductive carbon black and graphite, to construct a three-dimensional conductive network, thereby increasing the conductive pathways within the coating. Binder modification involves chemically modifying the binder in the coating, such as introducing polar functional groups or ion-conducting groups into the binder molecules to improve the compatibility between the binder and the carbon material, or to give the binder itself a certain degree of conductivity or ion-conductivity. Functional additives involve adding fluorinated compounds, pore-forming agents, and other auxiliaries to the slurry to improve the dispersibility of the carbon material, enhance the adhesion between the coating and the aluminum foil, or form a porous structure in the coating. Aluminum foil surface treatment involves forming micro-pits or rough structures on the aluminum foil surface through methods such as anodizing and plasma treatment to increase the contact area between the carbon coating and the aluminum foil, thereby improving interfacial bonding. Conductive polymer composites involve introducing conductive polymers such as polyaniline and polypyrrole into the carbon coating, utilizing the bridging effect of the conductive polymers to connect carbon particles and form a continuous conductive network.
[0004] However, existing technologies still have significant drawbacks: First, the carbon coating and aluminum foil rely solely on physical contact for bonding, making it difficult to further reduce the interfacial contact resistance; second, hydrophobic carbon materials in aqueous systems tend to agglomerate, failing to form a continuous and uniform conductive network; third, conductive polymers have poor compatibility with carbon materials, easily absorbing moisture and swelling in electrolyte environments, resulting in insufficient long-term cycling stability; and fourth, traditional aluminum foil surface pretreatment often uses strong acid electrolytes, leading to high wastewater treatment costs and significant environmental pollution. Summary of the Invention
[0005] To address the problems of high interfacial resistance, easy agglomeration of carbon materials, poor stability of conductive polymers, and environmentally unfriendly processes in existing technologies, this invention provides a highly conductive carbon-coated aluminum foil and its preparation process. The interfacial resistance is reduced through physical intercalation and chemical coordination, and the carbon materials are uniformly dispersed using surfactants. Additives and a segmented drying process enhance the conductivity and stability of the conductive polymer. Furthermore, an environmentally friendly electrolyte is used for aluminum foil etching, making the entire process green and pollution-free.
[0006] The objective of this invention can be achieved through the following technical solutions: In a first aspect, a highly conductive carbon-coated aluminum foil is provided, comprising an aluminum foil and a carbon coating disposed on at least one surface of the aluminum foil, wherein the surface of the aluminum foil has a micro-pit structure formed by electrochemical etching; The carbon coating is made of the following components in parts by weight: 3-5 parts of conductive carbon black; 1-2 parts of carbon nanotubes; Surfactant 0.02-0.1 parts; 10-15 parts of poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate dispersion; 0.1-0.3 parts of polyethylene glycol diglycidyl ether; 2-5 parts ethylene glycol; 3-5 parts of water-based acrylic emulsion; Citric acid 0.2-0.5 parts; 30-50 parts deionized water.
[0007] Furthermore, the carbon coating surface is replicated with the micro-pit structure of the aluminum foil surface, and the micro-pits are used to achieve physical interlocking between the carbon coating and the aluminum foil; the pore size of the micro-pits is 250-400nm and the depth is 0.3-0.8μm.
[0008] Furthermore, the conductive carbon black has a particle size of 25-45 nm and a specific surface area of 60-130 m². 2 / g; the carbon nanotubes have a diameter of 10-15nm and a length of 8-12μm.
[0009] Furthermore, the solid content of the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate dispersion is 1.0-1.3 wt%, wherein the mass ratio of poly(3,4-ethylenedioxythiophene) to polystyrene sulfonate is 1:2.5.
[0010] Poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate dispersion (hereinafter referred to as PEDOT:PSS).
[0011] Furthermore, the surfactant is sodium dodecyl sulfate (SDS) or tert-octylphenoxypolyethoxyethanol (Triton X-100); the solid content of the aqueous acrylic emulsion is 35-50 wt%.
[0012] Preferably, the solid content of the aqueous acrylic emulsion is 40-45 wt%.
[0013] Furthermore, the aluminum foil has a thickness of 10-20 μm, and the carbon coating has a thickness of 1-2 μm.
[0014] In a second aspect, a process for preparing highly conductive carbon-coated aluminum foil as described in the first aspect is provided, comprising the following steps: (1) The aluminum foil is placed in the sodium nitrate aqueous electrolyte for electrochemical etching. The etched aluminum foil is then cleaned and dried to obtain the pretreated aluminum foil. (2) Dissolve the surfactant in 10-15 parts of deionized water, add conductive carbon black and carbon nanotubes, stir and disperse for 10-20 minutes to obtain pre-modified carbon material; (3) Mix the pre-modified carbon material obtained in step (2) with ethylene glycol, stir and disperse evenly, add PEDOT:PSS dispersion, and continue to stir and disperse evenly; then add water-based acrylic emulsion, polyethylene glycol diglycidyl ether, citric acid and remaining deionized water in sequence, stir and disperse evenly to obtain carbon coating slurry; (4) Apply the carbon coating slurry obtained in step (3) to the surface of the aluminum foil after pretreatment in step (1); In this process, since the aluminum foil surface after pretreatment in step (1) has a micro-pit structure formed by electrochemical etching, the carbon coating slurry fills the micro-pits on the aluminum foil surface and replicates the micro-pit morphology during coating, thereby forming a micro-pit structure on the carbon coating surface and realizing the physical integration of the carbon coating and the aluminum foil.
[0015] (5) The coated aluminum foil is dried in sections and then rolled up to obtain highly conductive carbon-coated aluminum foil.
[0016] Furthermore, in step (1), the electrochemical etching employs a pulsed current with a peak current density of 3-4 A / dm². 2 The duty cycle is 35-45%, and the frequency is 200-500Hz; the concentration of the sodium nitrate aqueous solution is 2-3wt%; the etching time is 15-20 seconds; the etched aluminum foil is successively cleaned with deionized water, 0.2-0.3wt% dilute ammonia, and deionized water until neutral, and finally rinsed with hot water at 55-65℃ and dried at 80-100℃.
[0017] Further, in step (4), the coating method is microgravure coating, the coating speed is 20-40m / min, and the wet film thickness is 5-8μm.
[0018] Further, in step (5), the segmented drying includes a first segment of drying at 90-100℃ for 1-2 minutes and a second segment of drying at 110-130℃ for 2-3 minutes.
[0019] The beneficial effects of this invention are as follows: (1) This invention forms micro-pit morphology with a pore size of 250-400 nm and a depth of 0.3-0.8 μm by pulsed electrochemical etching of the aluminum foil surface. After coating with a carbon coating, the carbon coating surface replicates this micro-pit morphology, thus forming a micro-pit structure on the carbon coating surface. At the same time, citric acid is added to the carbon coating slurry. As a result, the micro-pit structure increases the contact area between the carbon coating and the aluminum foil, forming a physical interlock; the carboxyl groups in the citric acid molecules form chemical coordination with the alumina layer on the aluminum foil surface. The physical interlock and chemical coordination synergistically improve the interfacial bonding strength and reduce the electron transport resistance at the interface between the carbon coating and the aluminum foil, thereby significantly reducing the interfacial contact resistance to 1.5-1.9 mΩ·cm. 2 .
[0020] (2) Before preparing the slurry, the surfactant is dissolved in water, and conductive carbon black and carbon nanotubes are added and premixed. As a result, the oleophilic end of the surfactant molecule adsorbs onto the surface of the hydrophobic carbon material, while the hydrophilic end faces the aqueous phase, transforming the hydrophobic carbon material into a hydrophilic one, thus ensuring uniform dispersion in the aqueous slurry and preventing agglomeration. Furthermore, the aqueous acrylic emulsion exhibits good compatibility with the modified carbon material, and the carbon coating after drying possesses excellent adhesion and cohesion. These effects result in the uniform distribution of the carbon material within the carbon coating, forming a continuous and uniform conductive network. The resistance of the carbon coating is significantly reduced, with a sheet resistance of 1.3-1.7 ohms per square.
[0021] (3) In this invention, ethylene glycol and polyethylene glycol diglycidyl ether are added to the carbon coating slurry, and a segmented drying process is adopted. Thus, ethylene glycol assists in the dispersion of carbon materials, improving the compatibility between PEDOT:PSS and carbon materials, and induces microscopic phase separation between PEDOT and PSS, enriching PEDOT to form continuous conductive channels and improving the conductivity of PEDOT:PSS. During the drying process, polyethylene glycol diglycidyl ether undergoes a crosslinking reaction with the hydroxyl groups on the PEDOT:PSS molecular chain, crosslinking PEDOT:PSS into the carbon coating and preventing it from absorbing moisture, swelling, and falling off. Segmented drying ensures that moisture is fully removed in the first low-temperature zone, and the crosslinking reaction fully occurs in the second high-temperature zone. The above-mentioned ethylene glycol-induced phase separation, polyethylene glycol diglycidyl ether crosslinking fixation, and segmented drying constitute a composite modification system, which improves the long-term stability of PEDOT:PSS while maintaining high conductivity, with a resistance increase rate of 5-8% after 500 cycles.
[0022] (4) The present invention uses a low-concentration sodium nitrate aqueous solution as the electrolyte and performs electrochemical etching with pulse current. No strong acid waste liquid is generated, the etching time is short, and there are no harmful residues after cleaning. It is an environmentally friendly and economical pretreatment process. Detailed Implementation
[0023] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.
[0024] Example 1 I. Aluminum Foil Pretreatment A 15 μm thick aluminum foil was placed in a 2.5 wt% sodium nitrate aqueous solution electrolyte and electrochemically etched using a pulsed current with a peak current density of 3.5 A / dm³. 2 The etching process was performed at a duty cycle of 40%, a frequency of 350 Hz, and a processing time of 18 seconds. The etched aluminum foil was sequentially cleaned with deionized water, 0.25 wt% dilute ammonia, and then deionized water until neutral. Finally, it was washed with 60°C hot water and dried at 90°C to obtain the pretreated aluminum foil. Testing revealed a micro-pit structure on the aluminum foil surface, with a pit diameter of approximately 325 nm and a depth of approximately 0.55 μm. A carbon coating will be applied to the aluminum foil surface later. This carbon coating replicates the micro-pit morphology, thus forming a micro-pit structure on the carbon coating surface, further achieving physical integration between the aluminum foil and the carbon coating.
[0025] II. Pre-modification of carbon materials Weigh the following components by weight: 4 parts conductive carbon black, 1.5 parts carbon nanotubes, 0.06 parts surfactant (tert-octylphenoxypolyethoxyethanol, Triton X-100), and 12.5 parts deionized water.
[0026] The surfactant was dissolved in deionized water, and conductive carbon black and carbon nanotubes were added. The mixture was stirred and dispersed at 1500 rpm for 15 minutes to obtain the pre-modified carbon material.
[0027] III. Slurry Preparation Weigh the remaining components according to the following parts by weight: 12.5 parts PEDOT:PSS dispersion, 0.2 parts polyethylene glycol diglycidyl ether, 3.5 parts ethylene glycol, 4 parts aqueous acrylic emulsion, 0.35 parts citric acid, and 27.5 parts deionized water.
[0028] The pre-modified carbon material obtained in step two was mixed with ethylene glycol and stirred at 1200 rpm for 5 minutes. PEDOT:PSS dispersion was added and stirred at 1200 rpm for 10 minutes. Then, aqueous acrylic emulsion, polyethylene glycol diglycidyl ether, citric acid and deionized water were added in sequence, stirring for 5 minutes after each addition. Finally, the mixture was stirred at 1000 rpm for 30 minutes to obtain the carbon coating slurry.
[0029] IV. Coating The carbon coating slurry obtained in step three was applied to the surface of the aluminum foil after pretreatment in step one using a micro-gravure coating method. The coating speed was 30 m / min and the wet film thickness was 6.5 μm.
[0030] Since the aluminum foil surface after the pretreatment in step one has a micro-pit structure formed by electrochemical etching, the carbon coating slurry fills the micro-pits on the aluminum foil surface and replicates the morphology of the micro-pits during coating, thereby forming a micro-pit structure on the carbon coating surface.
[0031] V. Drying The coated aluminum foil is sent into a segmented drying oven. The first segment is dried at 95°C for 1.5 minutes, and the second segment is dried at 120°C for 2.5 minutes. After drying, it is rolled up to obtain highly conductive carbon-coated aluminum foil.
[0032] Example 2 I. Aluminum Foil Pretreatment A 10 μm thick aluminum foil was placed in a 2.0 wt% sodium nitrate aqueous solution electrolyte and electrochemically etched using a pulsed current with a peak current density of 3.0 A / dm³. 2 The duty cycle was 35%, the frequency was 200Hz, and the processing time was 20 seconds. The etched aluminum foil was sequentially washed with deionized water, 0.2wt% dilute ammonia, and then deionized water until neutral. Finally, it was washed with hot water at 55℃ and dried at 80℃ to obtain the pretreated aluminum foil. Testing revealed the formation of a micropit structure on the aluminum foil surface, with a pit diameter of approximately 260nm and a depth of approximately 0.35μm.
[0033] II. Pre-modification of carbon materials Weigh the following components by weight: 3 parts conductive carbon black, 1 part carbon nanotubes, 0.02 parts surfactant (tert-octylphenoxypolyethoxyethanol), and 10 parts deionized water.
[0034] The surfactant was dissolved in deionized water, and conductive carbon black and carbon nanotubes were added. The mixture was stirred and dispersed at 2000 rpm for 20 minutes to obtain the pre-modified carbon material.
[0035] III. Slurry Preparation Weigh the remaining components according to the following parts by weight: 10 parts PEDOT:PSS dispersion, 0.1 parts polyethylene glycol diglycidyl ether, 2 parts ethylene glycol, 3 parts aqueous acrylic emulsion, 0.2 parts citric acid, and 20 parts deionized water.
[0036] The pre-modified carbon material obtained in step two was mixed with ethylene glycol and stirred at 800 rpm for 5 minutes. PEDOT:PSS dispersion was added and stirred at 800 rpm for 10 minutes. Then, aqueous acrylic emulsion, polyethylene glycol diglycidyl ether, citric acid and deionized water were added in sequence, and stirred for 5 minutes after each addition. Finally, the mixture was stirred at 800 rpm for 40 minutes to obtain the carbon coating slurry.
[0037] IV. Coating The carbon coating slurry obtained in step three was applied to the surface of the aluminum foil after pretreatment in step one using a micro-gravure coating method. The coating speed was 20 m / min and the wet film thickness was 5 μm.
[0038] V. Drying The coated aluminum foil is sent into a segmented drying oven. The first segment is dried at 90°C for 2 minutes, and the second segment is dried at 110°C for 3 minutes. After drying, it is rolled up to obtain highly conductive carbon-coated aluminum foil.
[0039] Example 3 I. Aluminum Foil Pretreatment A 20 μm thick aluminum foil was placed in a 3.0 wt% sodium nitrate aqueous solution electrolyte and electrochemically etched using a pulsed current with a peak current density of 4.0 A / dm³. 2 The duty cycle was 45%, the frequency was 500 Hz, and the processing time was 15 seconds. The etched aluminum foil was sequentially cleaned with deionized water, 0.3 wt% dilute ammonia, and then deionized water until neutral. Finally, it was washed with 65°C hot water and dried at 100°C to obtain the pretreated aluminum foil. Testing revealed the formation of a micropit structure on the aluminum foil surface, with a pit diameter of approximately 380 nm and a depth of approximately 0.75 μm.
[0040] II. Pre-modification of carbon materials Weigh the following components by weight: 5 parts conductive carbon black, 2 parts carbon nanotubes, 0.1 parts surfactant (sodium dodecyl sulfate, SDS), and 15 parts deionized water.
[0041] The surfactant was dissolved in deionized water, and conductive carbon black and carbon nanotubes were added. The mixture was stirred and dispersed at 1000 rpm for 20 minutes to obtain the pre-modified carbon material.
[0042] III. Slurry Preparation Weigh the remaining components according to the following parts by weight: 15 parts PEDOT:PSS dispersion, 0.3 parts polyethylene glycol diglycidyl ether, 5 parts ethylene glycol, 5 parts aqueous acrylic emulsion, 0.5 parts citric acid, and 35 parts deionized water.
[0043] The pre-modified carbon material obtained in step two was mixed with ethylene glycol and stirred at 1500 rpm for 5 minutes. PEDOT:PSS dispersion was added and stirred at 1500 rpm for 10 minutes. Then, aqueous acrylic emulsion, polyethylene glycol diglycidyl ether, citric acid and deionized water were added in sequence, stirring for 5 minutes after each addition. Finally, the mixture was stirred at 1500 rpm for 20 minutes to obtain the carbon coating slurry.
[0044] IV. Coating The carbon coating slurry obtained in step three was applied to the surface of the aluminum foil after pretreatment in step one using a micro-gravure coating method. The coating speed was 40 m / min and the wet film thickness was 8 μm.
[0045] V. Drying The coated aluminum foil is sent into a segmented drying oven. The first segment is dried at 100°C for 1 minute, and the second segment is dried at 130°C for 2 minutes. After drying, it is rolled up to obtain highly conductive carbon-coated aluminum foil.
[0046] Example 4 I. Aluminum Foil Pretreatment A 15 μm thick aluminum foil was placed in a 2.5 wt% sodium nitrate aqueous solution electrolyte and electrochemically etched using a pulsed current with a peak current density of 3.5 A / dm³. 2 The duty cycle was 40%, the frequency was 350 Hz, and the processing time was 18 seconds. The etched aluminum foil was sequentially washed with deionized water, 0.25 wt% dilute ammonia, and then with deionized water until neutral. Finally, it was washed with 60°C hot water and dried at 90°C to obtain the pretreated aluminum foil. Testing revealed the formation of a micropit structure on the aluminum foil surface, with a pit diameter of approximately 325 nm and a depth of approximately 0.55 μm.
[0047] II. Pre-modification of carbon materials Weigh the following components by weight: 4 parts conductive carbon black, 1.5 parts carbon nanotubes, 0.06 parts surfactant (sodium dodecyl sulfate), and 12.5 parts deionized water.
[0048] The surfactant was dissolved in deionized water, and conductive carbon black and carbon nanotubes were added. The mixture was stirred and dispersed at 1500 rpm for 15 minutes to obtain the pre-modified carbon material.
[0049] III. Slurry Preparation Weigh the remaining components according to the following parts by weight: 12.5 parts PEDOT:PSS dispersion, 0.2 parts polyethylene glycol diglycidyl ether, 3.5 parts ethylene glycol, 4 parts aqueous acrylic emulsion, 0.35 parts citric acid, and 27.5 parts deionized water.
[0050] The pre-modified carbon material obtained in step two was mixed with ethylene glycol and stirred at 1200 rpm for 5 minutes. PEDOT:PSS salt dispersion was added and stirred at 1200 rpm for 10 minutes. Then, aqueous acrylic emulsion, polyethylene glycol diglycidyl ether, citric acid and the remaining deionized water were added in sequence, stirring for 5 minutes after each addition. Finally, the mixture was stirred at 1000 rpm for 30 minutes to obtain the carbon coating slurry.
[0051] IV. Coating The carbon coating slurry obtained in step three was applied to the surface of the aluminum foil after pretreatment in step one using a micro-gravure coating method. The coating speed was 30 m / min and the wet film thickness was 6.5 μm.
[0052] V. Drying The coated aluminum foil is sent into a segmented drying oven. The first segment is dried at 95°C for 1.5 minutes, and the second segment is dried at 120°C for 2.5 minutes. After drying, it is rolled up to obtain highly conductive carbon-coated aluminum foil.
[0053] It should be noted that sodium dodecyl sulfate is added to the carbon coating slurry in this embodiment. It is recommended that the carbon coating slurry be used within 24 hours after preparation, or be prepared and used immediately.
[0054] Example 5 I. Aluminum Foil Pretreatment A 15 μm thick aluminum foil was placed in a 2.5 wt% sodium nitrate aqueous solution electrolyte and electrochemically etched using a pulsed current with a peak current density of 3.5 A / dm³. 2 The duty cycle was 40%, the frequency was 350Hz, and the processing time was 18 seconds. The etched aluminum foil was then washed sequentially with deionized water, 0.25wt% dilute ammonia, and deionized water until neutral. Finally, it was washed with 60℃ hot water and dried at 90℃ to obtain the pretreated aluminum foil.
[0055] II. Pre-modification of carbon materials Weigh the following components by weight: 3.5 parts conductive carbon black, 1.2 parts carbon nanotubes, 0.06 parts surfactant (tert-octylphenoxypolyethoxyethanol, Triton X-100), and 12.5 parts deionized water.
[0056] The surfactant was dissolved in deionized water, and conductive carbon black and carbon nanotubes were added. The mixture was stirred at 1500 rpm for 15 minutes to obtain the pre-modified carbon material.
[0057] III. Slurry Preparation Weigh the remaining components according to the following parts by weight: 12.5 parts PEDOT:PSS dispersion, 0.2 parts polyethylene glycol diglycidyl ether, 3.5 parts ethylene glycol, 4 parts aqueous acrylic emulsion, 0.3 parts citric acid, and 27.5 parts deionized water.
[0058] The pre-modified carbon material obtained in step two was mixed with ethylene glycol and stirred at 1200 rpm for 5 minutes. PEDOT:PSS dispersion was added and stirred at 1200 rpm for 10 minutes. Then, aqueous acrylic emulsion, polyethylene glycol diglycidyl ether, citric acid and deionized water were added in sequence, stirring for 5 minutes after each addition. Finally, the mixture was stirred at 1000 rpm for 30 minutes to obtain the carbon coating slurry.
[0059] IV. Coating The carbon coating slurry obtained in step three was applied to the surface of the aluminum foil after pretreatment in step one using a micro-gravure coating method. The coating speed was 30 m / min and the wet film thickness was 6.5 μm.
[0060] V. Drying The coated aluminum foil is sent into a segmented drying oven. The first segment is dried at 95°C for 1.5 minutes, and the second segment is dried at 120°C for 2.5 minutes. After drying, it is rolled up to obtain highly conductive carbon-coated aluminum foil.
[0061] Example 6 I. Aluminum Foil Pretreatment A 20 μm thick aluminum foil was placed in a 3.0 wt% sodium nitrate aqueous solution electrolyte and electrochemically etched using a pulsed current with a peak current density of 4.0 A / dm³. 2 The duty cycle was 45%, the frequency was 500Hz, and the processing time was 15 seconds. The etched aluminum foil was then washed sequentially with deionized water, 0.3wt% dilute ammonia, and deionized water until neutral. Finally, it was washed with 65℃ hot water and dried at 100℃ to obtain the pretreated aluminum foil.
[0062] II. Pre-modification of carbon materials Weigh the following components by weight: 4.5 parts conductive carbon black, 1.8 parts carbon nanotubes, 0.08 parts surfactant (sodium dodecyl sulfate, SDS), and 15 parts deionized water.
[0063] The surfactant was dissolved in deionized water, and conductive carbon black and carbon nanotubes were added. The mixture was stirred at 1000 rpm for 20 minutes to obtain the pre-modified carbon material.
[0064] III. Slurry Preparation Weigh the remaining components according to the following parts by weight: 15 parts PEDOT:PSS dispersion, 0.25 parts polyethylene glycol diglycidyl ether, 5 parts ethylene glycol, 5 parts aqueous acrylic emulsion, 0.4 parts citric acid, and 35 parts deionized water.
[0065] The pre-modified carbon material obtained in step two was mixed with ethylene glycol and stirred at 1500 rpm for 5 minutes. PEDOT:PSS dispersion was added and stirred at 1500 rpm for 10 minutes. Then, aqueous acrylic emulsion, polyethylene glycol diglycidyl ether, citric acid and deionized water were added in sequence, stirring for 5 minutes after each addition. Finally, the mixture was stirred at 1500 rpm for 20 minutes to obtain the carbon coating slurry.
[0066] IV. Coating The carbon coating slurry obtained in step three was applied to the surface of the aluminum foil after pretreatment in step one using a micro-gravure coating method. The coating speed was 40 m / min and the wet film thickness was 8 μm.
[0067] V. Drying The coated aluminum foil is sent into a segmented drying oven. The first segment is dried at 100°C for 1 minute, and the second segment is dried at 130°C for 2 minutes. After drying, it is rolled up to obtain highly conductive carbon-coated aluminum foil.
[0068] Comparative Example 1 Based on Example 1, the aluminum foil was not subjected to the electrochemical etching treatment in step (1), but was used directly after being cleaned with deionized water, and no citric acid was added. The other conditions were the same as in Example 1.
[0069] Comparative Example 2 Based on Example 1, citric acid was not added, and all other conditions were the same as in Example 1.
[0070] Comparative Example 3 Based on Example 1, without adding surfactant, conductive carbon black and carbon nanotubes were directly added to deionized water and stirred to mix, with the remaining conditions being the same as in Example 1.
[0071] Comparative Example 4 Based on Example 1, ethylene glycol and polyethylene glycol diglycidyl ether were not added, and instead of segmented drying, constant temperature drying (single-segment drying at 120°C for 4 minutes) was used, with the remaining conditions being the same as in Example 1.
[0072] Comparative Example 5 Based on Example 1, ethylene glycol was not added, and all other conditions were the same as in Example 1.
[0073] Comparative Example 6 Based on Example 1, without the addition of polyethylene glycol diglycidyl ether, all other conditions are the same as in Example 1.
[0074] Comparative Example 7 Carbon-coated aluminum foil was prepared according to the method in document CN118756284A.
[0075] Comparative Example 8 Based on Example 1, citric acid was replaced with oxalic acid, and all other conditions were the same as in Example 1.
[0076] Comparative Example 9 Based on Example 1, citric acid was replaced with tartaric acid, and all other conditions were the same as in Example 1.
[0077] Comparative Example 10 Based on Example 1, the amount of citric acid was adjusted to 0.18 parts, and the other conditions were the same as in Example 1.
[0078] Comparative Example 11 Based on Example 1, the amount of citric acid was adjusted to 0.7 parts, and the other conditions were the same as in Example 1.
[0079] Performance testing I. Testing Methods 1. Carbon Coating Sheet Resistance Test Using a four-probe tester, the carbon-coated aluminum foil sample to be tested is placed on the insulation test platform with the carbon coating facing upwards. The four probes are pressed vertically against the surface of the carbon coating, a set pressure is applied, and the sheet resistance value of the carbon coating (ohms per square) is recorded.
[0080] 2. Interface contact resistance test Referring to the MIL-DTL-81706B standard, a chemical conversion film contact resistance tester was used. The carbon-coated aluminum foil sample to be tested was placed on the lower electrode of the test fixture, with the carbon coating facing upwards. An aluminum foil of the same size was placed on the carbon coating surface as the upper electrode. A constant pressure of 200-600 kPa was applied, and the total resistance was measured using the four-terminal method. The interfacial contact resistance value (mΩ·cm) was calculated based on the contact area of the upper and lower electrodes. 2 ).
[0081] 3. Resistance rise rate test after 500 cycles The carbon-coated aluminum foil to be tested was cut into circular pieces, coated with lithium iron phosphate positive electrode slurry of the same formulation and solid content under the same process conditions, dried and rolled to serve as the positive electrode sheet. Using a lithium metal sheet as the counter electrode, a polypropylene microporous membrane as the separator, and 1M LiPF6 electrolyte (solvent with a volume ratio of EC / EMC / DMC of 1:1:1), CR2032 coin cells were assembled in an argon glove box.
[0082] The assembled battery was placed on the charge-discharge test system and subjected to constant current charge-discharge test within a voltage range of 2.5-3.8V. The battery was first activated at 0.2C for 3 cycles, and then subjected to 500 charge-discharge cycles at 1C. After the first and 500th cycles, the battery was disassembled, the positive electrode was removed, gently rinsed with dimethyl carbonate solvent and dried, and the interface contact resistance was tested.
[0083] Resistance rise rate = (interface contact resistance after 500th cycle - interface contact resistance after 1st cycle) / interface contact resistance after 1st cycle × 100%.
[0084] II. Test Results Table 1. Performance test results of the examples and comparative examples.
[0085] The test results show that the sheet resistance of the carbon coating in Examples 1-6 is 1.3-1.7 ohms per square, and the interface contact resistance is 1.5-1.9 mΩ·cm. 2 After 500 cycles, the resistance increase rate was 5-8%, demonstrating excellent conductivity and cycle stability. Comparative Example 1, lacking both micropit etching and citric acid, showed an interface contact resistance as high as 2.9 mΩ·cm. 2 Comparative Example 2 only lacked citric acid, and its interfacial contact resistance was 2.6 mΩ·cm. 2 The resistance was still significantly higher than in the examples, indicating that neither physical intercalation nor chemical coordination alone could achieve optimal interfacial bonding; only through synergy of both could a low interfacial contact resistance be achieved. Comparative Example 3, lacking surfactant pre-modification, resulted in uneven dispersion of the carbon material, with a coating sheet resistance as high as 2.7 ohms per block. This demonstrates that surfactant pre-modification provides the structural basis for subsequent PEDOT:PSS coating and conductive network construction; without this step, the conductivity of subsequent components cannot be fully realized. Comparative Example 4, lacking ethylene glycol, PEGDGE, and segmented drying, had a coating sheet resistance as high as 3.4 ohms per block, with a resistance increase rate of 26% after cycling. Comparative Example 5, lacking only ethylene glycol, had a coating sheet resistance of 2.2 ohms per block, with a resistance increase rate of 19% after cycling, indicating that the conductivity of PEDOT:PSS could not be fully realized without ethylene glycol. Comparative Example 6, lacking only PEGDGE, had a resistance increase rate of 9% after cycling. Single modification methods alone cannot achieve both conductivity and stability; only through synergy of all three can excellent conductivity and cycling stability be obtained simultaneously. Comparative Example 7 was prepared according to the method in CN118756284A, and its interfacial contact resistance was 2.8 mΩ·cm. 2 The resistance increase rate after cycling was 15%, which was worse than that of Example 1. In Comparative Examples 8 and 9, after replacing citric acid with oxalic acid or tartaric acid, the interfacial contact resistance increased to 2.4 mΩ·cm, respectively.2 and 2.3mΩ·cm 2 After cycling, the resistance increased by 12% and 11% respectively, while the adhesion decreased, proving that other organic acids cannot replace the chemical coordination effect of citric acid. In Comparative Example 10, with a reduced amount of citric acid, the interfacial contact resistance increased to 2.2 mΩ·cm. 2 After cycling, the resistance increase rate rose to 10%, and the performance deteriorated. In Comparative Example 11, with an increased amount of citric acid, the interfacial contact resistance was 2.1 mΩ·cm. 2 The resistance increase rate after cycling was 10%, which was not further improved compared to Example 1.
[0086] To further verify the technical effectiveness, an adhesion test was conducted using Example 1 as an example. 1. Adhesion test (pull-out test) Following the GB / T 5210-2006 standard, an adhesion tester was used. The carbon-coated aluminum foil sample to be tested was cut to an appropriate size, and a pull-out head was adhered to the carbon coating surface using a special adhesive. After the adhesive cured, a vertical pull force was applied at a constant rate not exceeding 1 MPa / s. The maximum pull force when the carbon coating peeled off the aluminum foil surface was recorded, and this force was divided by the pull-out head area to obtain the adhesion value (MPa). After the test, the type of failure was observed and recorded as adhesion failure (destruction at the interface between the carbon coating and the aluminum foil) or cohesive failure (destruction within the carbon coating).
[0087] Table 2
[0088] The results showed that Example 1 exhibited excellent carbon coating adhesion strength. Comparative Example 2, without the addition of citric acid, had an adhesion of only 3.8 MPa. Comparative Example 7, prepared according to the method in document CN118756284A, had an adhesion of 5.2 MPa, lower than that of Example 1. In Comparative Examples 8 and 9, after replacing citric acid with oxalic acid or tartaric acid, the adhesion decreased to 4.0 MPa and 4.2 MPa, respectively. In Comparative Example 10, the amount of citric acid was reduced, and the adhesion decreased to 5.0 MPa. In Comparative Example 11, the amount of citric acid was increased, and the adhesion remained at 5.8 MPa, without further improvement.
[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A highly conductive carbon-coated aluminum foil, comprising an aluminum foil and a carbon coating disposed on at least one surface of the aluminum foil, characterized in that, The aluminum foil surface has a micro-pit structure formed by electrochemical etching; The carbon coating is made of the following components in parts by weight: 3-5 parts of conductive carbon black; 1-2 parts of carbon nanotubes; Surfactant 0.02-0.1 parts; 10-15 parts of poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate dispersion; 0.1-0.3 parts of polyethylene glycol diglycidyl ether; 2-5 parts ethylene glycol; 3-5 parts of water-based acrylic emulsion; Citric acid 0.2-0.5 parts; 30-50 parts deionized water.
2. The highly conductive carbon-coated aluminum foil according to claim 1, characterized in that, The carbon coating surface is replicated with the micro-pit structure of the aluminum foil surface. The micro-pits are used to achieve physical bonding between the carbon coating and the aluminum foil. The pore size of the micro-pits is 250-400nm and the depth is 0.3-0.8μm.
3. The highly conductive carbon-coated aluminum foil according to claim 1, characterized in that, The conductive carbon black has a particle size of 25-45 nm and a specific surface area of 60-130 m². 2 / g; the carbon nanotubes have a diameter of 10-15nm and a length of 8-12μm.
4. The highly conductive carbon-coated aluminum foil according to claim 1, characterized in that, The solid content of the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate dispersion is 1.0-1.3 wt%, wherein the mass ratio of poly(3,4-ethylenedioxythiophene) to polystyrene sulfonate is 1:2.
5.
5. The highly conductive carbon-coated aluminum foil according to claim 1, characterized in that, The surfactant is sodium dodecyl sulfate or tert-octylphenoxypolyethoxyethanol; the solid content of the aqueous acrylic emulsion is 35-50 wt%.
6. The highly conductive carbon-coated aluminum foil according to claim 1, characterized in that, The aluminum foil has a thickness of 10-20 μm, and the carbon coating has a thickness of 1-2 μm.
7. A process for preparing a highly conductive carbon-coated aluminum foil as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) The aluminum foil is placed in the sodium nitrate aqueous electrolyte for electrochemical etching. The etched aluminum foil is then cleaned and dried to obtain the pretreated aluminum foil. (2) Dissolve the surfactant in 10-15 parts of deionized water, add conductive carbon black and carbon nanotubes, stir and mix for 10-20 minutes to obtain pre-modified carbon material; (3) Mix the pre-modified carbon material obtained in step (2) with ethylene glycol, stir and disperse evenly, add poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate dispersion, and continue to stir and disperse evenly; then add water-based acrylic emulsion, polyethylene glycol diglycidyl ether, citric acid and remaining deionized water in sequence, stir and disperse evenly to obtain carbon coating slurry; (4) Apply the carbon coating slurry obtained in step (3) to the surface of the aluminum foil after pretreatment in step (1); (5) The coated aluminum foil is dried in sections and then rolled up to obtain highly conductive carbon-coated aluminum foil.
8. The preparation process of the highly conductive carbon-coated aluminum foil according to claim 7, characterized in that, In step (1), the electrochemical etching uses pulsed current with a peak current density of 3-4 A / dm³. 2 The duty cycle is 35-45%, and the frequency is 200-500Hz; the concentration of the sodium nitrate aqueous solution is 2-3wt%; the etching time is 15-20 seconds; the etched aluminum foil is successively cleaned with deionized water, 0.2-0.3wt% dilute ammonia, and deionized water until neutral, and finally rinsed with hot water at 55-65℃ and dried at 80-100℃.
9. The preparation process of the highly conductive carbon-coated aluminum foil according to claim 7, characterized in that, In step (4), the coating method is microgravure coating, the coating speed is 20-40m / min, and the wet film thickness is 5-8μm.
10. The preparation process of the highly conductive carbon-coated aluminum foil according to claim 7, characterized in that, In step (5), the segmented drying includes the first segment drying at 90-100℃ for 1-2 minutes and the second segment drying at 110-130℃ for 2-3 minutes.
Citation Information
Patent Citations
Carbon-coated aluminum foil with surface micro-pit modeling and preparation process thereof
CN118756284A